SPIRITUAL LEADERSHIP AND JOB SATISFACTION OF TEACHING AND NON-TEACHING PERSONNEL OF PARTIDO STATE UNIVERSITY - Delfino, Armando P (PEOPLE: International Journal of Social Sciences, 2019)
School leadership is tasked to help faculty developed their potentials so that they could contribute to the attainment of the objectives of the university. Failure of the leadership to inspire its people would result to low performance of the institution. This study analyzed the correlation between spiritual leadership and job satisfaction of the teaching and non-teaching personnel of Partido State University.The study used descriptive-correlational research design to describe the relationship between spiritual leadership and job satisfaction. The Data were treated through Statistical Package for Social Sciences (SPSS). Focused Group Discussion (FGD) was used to verify and gather additional data from the respondents. The researchers used standardized questionnaires on Spiritual Leadership and Job Satisfaction. The respondents of the study were the 81 faculty members and 63 non-teaching personnel of Partido State University.Findings of the study revealed that the extent of spiritual leadership in Partido State University was high and the job satisfaction was slightly satisfying. The results of the t-test revealed that among the seven dimensions of Spiritual Leadership altruistic love and productivity were found to be significantly different between the teaching and the non-teaching personnel. Furthermore, Spiritual Leadership was found to have a weak correlation to job satisfaction of the teaching and non-teaching personnel of Partido State University. The university officials should continue reaching out to its employees and communicate clearly the directions of the institution. Furthermore, the fair and just working environment should be strengthened so that, it would be felt by all employees. Enough support should be given to all employees based on their needs to increase their productivity. Spiritual leadership should be strengthened to promote healthy working environment and increase job satisfaction among employees.